MENINGKATKAN KOMPETENSI AKADEMIK MAHASISWA MELALUI WORKSHOP PEMANFAATAN MENDELEY SEBAGAI ALAT REFERENSI - Cahyadi, Wahyu; Ariyanto, Sudirman; Nugraha, Ata (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2023)
Vocational Education in Automotive Technology (VEAT) plays a crucial role in preparing students for the industry. The ability to compose scholarly works is a vital aspect, reflecting the assessment of learning and the development of analytical, synthesis, and information literacy skills. VEAT students often encounter challenges in using the Mendeley reference management tool, potentially reducing the quality of scholarly works and increasing the risk of plagiarism. There is a knowledge gap among VEAT students regarding the use of Mendeley, necessitating strategic steps to enhance their understanding and skills. This community engagement initiative introduces in-depth training and mentoring on Mendeley for VEAT students, aiming to improve research efficiency, academic literacy, and confidence in composing scholarly works. The implementation method involves training design, field observations, preliminary studies, and the evaluation of students' understanding before and after training. Implementation includes Mendeley installation, account creation, and application usage, with evaluations covering several key indicators. Results indicate that this community engagement activity successfully enhances the understanding and skills of VEAT students in reference management, evidenced by significant improvements in all evaluation indicators. The average score increased by 62%, reflecting consistent improvement. Despite the positive outcomes, attention to technical constraints and consideration for extending training duration is necessary. Continuous evaluation is required to ensure the effectiveness of this community engagement initiative, expected to contribute positively to the quality of vocational education in the automotive technology field.